Who votes for vox? Socioeconomic profiles and electoral shifts in the region of Madrid - Roig, Rosa; Espinosa, Priscila; Pavía, Jose M. (Frontiers in Political Science, 2025)
IntroductionThe rise of the radical right in Europe is frequently interpreted through the “modernization losers” framework. This study examines whether this theory explains Vox's electoral breakthrough in the Region of Madrid (RoM).MethodsUsing a comprehensive database combining income variables and electoral results at the census-section level, the analysis estimates vote-transfer matrices through ecological inference to identify the sociodemographic profile of Vox voters in both general and regional elections from 2016 to 2023.ResultsFindings show that Vox's emergence and initial expansion in the RoM were primarily driven by the upper-middle and right-middle classes, contradicting the modernization-losers hypothesis. Only later—after the COVID-19 outbreak and the imposition of mobility restrictions in 2020—did modernization losers begin to join its electorate.DiscussionAlthough the study focuses mainly on electoral supply, it also incorporates demand-side dynamics. The interaction between these dimensions, together with contextual conditions, helps explain the evolution of Vox's support over time. Moreover, this support is strongly conditioned by the characteristics and discourse of the competing candidate from the traditional right.